Analysis Of Main Characters in the Film The Little Prince by Mark Osborne 2015 - Anisa Andini Putri; Andri Purwanto (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This study discusses several findings regarding the analysis of the main characters in the little prince film. This study discusses the main character described by Florence Littauer and uses a qualitative descriptive method. According to Florence Littauer in the Personality Plus book, there are four personality categories, namely: (1) Sanguine type with a percentage of 42% of the 11 data found, (2) Melancholic Type with a percentage of 8% of the 2 data found, (3) Phlegmatic type with a percentage 31% of the 8 data found, (4) Choleric type with a percentage of 19% of the 5 data found.